Assessing Public Policies and Assets That Affect Obesity Risk While Building New Public Health Partnerships, New Hampshire, 2011 - Ludmila Anderson, MD, MPH; Scot Foster, BS; Regina Flynn, BS; Mindy Fitterman, MEd, RD (Preventing Chronic Disease, 2013)
The New Hampshire Obesity Prevention Program and the 9 New Hampshire regional planning commissions assessed the state’s obesity-related policies and assets by using community measures recommended by the Centers for Disease Control and Prevention. A self-administered questionnaire that focused on policies and assets that promote healthful eating, physical activity, and breast-feeding was sent to 234 municipalities; 59% responded (representing 73% of the state’s population). Of the municipalities that responded, 52% had sidewalks, 22% had bicycle lanes, none had nutrition standards, and 4% had a policy supporting breastfeeding. Through collaboration, we gathered baseline information that can be used to set priorities and assess progress over time.